Analysis of Legal Protection for Children as Victims of Domestic Violence (KDRT) by Parents - Muhammad Amin; Suriansyah Murhaini; Claudia Yuni Pramita; Yacob Ferdinan Martono (Jurnal Daulat Hukum, 2026)
This study aims to analyze the forms of legal protection for children who are victims of domestic violence committed by their parents. As a vulnerable group, children have the right to protection from all forms of violence, whether physical, mental, or neglect, as stipulated in Law Number 35 of 2014 concerning Child Protection and Law Number 23 of 2004 concerning the Elimination of Domestic Violence. However, there are still many cases of domestic violence against children that are not properly managed, due to weak law enforcement and a lack of awareness among the public. The method used in this study is normative juridical analysis of relevant legislation and court decisions. The findings of this study show that even though there are existing legal instruments, the implementation of protection for children who are victims of domestic violence has not been running well because it faces various structural and social challenges. Therefore, it is very important to reform policies and increase the role of child protection agencies and law enforcement agencies to provide comprehensive protection to children who are victims of domestic violence.